METODE IBC SEBAGAI KUNCI BERBICARA PROFESIONAL DALAM PUBLIC SPEAKING BATCH 7 BAGI MAHASISWA UNIVERSITAS NUSA PUTRA SUKABUMI - Hesri Mintawati; Bonse Aris Mandala; Thessa Tri Astuty; Md Shodiq; Asep Hermawan (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Public speaking is an important communication skill in today's digital era. This study aims to analyze the effectiveness of the IBC (Introduction, Body, Conclusion) method in training students' public speaking skills. The research was conducted in batch 7 of public speaking training at Nusa Putra University Sukabumi with 40 students participating. The research method is qualitative with observation, interview and documentation study techniques. The results showed that the IBC method was very effective in equipping participants to become professional speakers. Participants were able to create an attention-grabbing introduction, deliver the content systematically, and make a conclusion that summarizes the main points. Regular application of the IBC method is proven to improve students' public speaking skills. This study recommends that the IBC method be applied to public speaking training to produce professional speakers in the digital era